SUPERVISI DAN PENGAWASAN KEPALA SEKOLAH DI SEKOLAH - Hayatunufus Hayatunufus; Muhammad Nawafil Akbar (CV. ADIBA ASIHA AMIRA, 2023)
This research is a library research, there are two sources of data that will be used in this study. First, primary data sources, namely reference books which are the main source of research. Second, secondary data sources are supporting reference sources in this study. The data collection method used is the documentation method. The data analysis technique used is content analysis technique which is translated into content analysis or content study. The results of the research are that supervision carried out by school principals is useful for improving the quality of the educational institution itself and supervision of supervisors as an effort to improve the quality of processes and learning outcomes by increasing the competence and skills of teachers through the professional guidance of school supervisors